Simplify the following expression. (x + 8)^3

Question

Asked 11/30/2014 9:04:53 PM

Updated 12/1/2014 2:52:04 AM

1 Answer/Comment

This conversation has been flagged as incorrect.

Flagged by yeswey [12/1/2014 2:50:22 AM]

s

Rating

8

(x + 8)^3

= (x + 8)^2 * (x + 8)

= (x^2 + 16x + 64)(x + 8)

= x^3 + 8x^2 + 16x^2 + 128x + 64x + 512

= x^3 + 24x^2 + 192x + 512

= (x + 8)^2 * (x + 8)

= (x^2 + 16x + 64)(x + 8)

= x^3 + 8x^2 + 16x^2 + 128x + 64x + 512

= x^3 + 24x^2 + 192x + 512

Added 12/1/2014 2:52:04 AM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [12/1/2014 3:16:05 AM]

Select the product of (3x - 4)(2x + 8).

Question

Updated 11/30/2014 9:16:53 PM

1 Answer/Comment

(3x - 4)(2x + 8)

= 6x^2 + 24x -8x - 32

= 6x^2 + 16x - 32

= 6x^2 + 24x -8x - 32

= 6x^2 + 16x - 32

Added 11/30/2014 9:16:47 PM

This answer has been confirmed as correct and helpful.

Select the product of (3x - 4)(2x + 8). **Weegy:** (3x - 4)(2x + 8)
= 6x^2 + 24x - 8x - 32
= 6x^2 + 16x - 32 (More)

Question

Expert Answered

Updated 11/30/2014 9:55:07 PM

0 Answers/Comments

Select the product of (7x + 1)(7x - 1). **Weegy:** (7x + 1)(7x - 1)
= 49x^2 - 7x + 7x - 1
= 49x^2 - 1 (More)

Question

Expert Answered

Updated 11/30/2014 9:53:52 PM

0 Answers/Comments

Select the product of (6x + 9)(x2 - 3x + 3). **Weegy:** (6x + 9)(x^2 - 3x + 3)
= 6x^3 - 18x^2 + 9x^2 + 18x - 27x + 27
= 6x^3 - 9x^2 - 9x + 27 (More)

Question

Expert Answered

Updated 11/30/2014 9:52:33 PM

0 Answers/Comments

Select the product of (-6x^4y)(x^3y^9). **Weegy:** (-6x^4y)(x^3y^9)
= -6x^7y^10 (More)

Question

Expert Answered

Updated 11/30/2014 9:51:33 PM

0 Answers/Comments

34,468,739

questions answered

S

L

1

1

1

1

1

1

1

1

1

1

1

1

1

1

1

1

1

P

1

L

P

1

Points 835 [Total 6708] Ratings 19 Comments 645 Invitations 0 Online

There are no comments.